Non-noble metal high-electric-response ammonia synthesis catalyst and ammonia synthesis method
By using Ce0.4Al0.1Zr0.5O1.95 support and liquid phase reduction method, the problems of low Faraday efficiency and high catalyst cost in the electrocatalytic ammonia synthesis process are solved, and efficient ammonia synthesis under low temperature and low pressure conditions are achieved, reducing production costs and suitable for industrial applications.
Patent Information
- Application Number
- CN202510036145.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-04
AI Technical Summary
The existing electrocatalytic ammonia synthesis process has problems of low Faraday efficiency and high catalyst cost, especially the scarcity and high price of precious metal catalysts limit their large-scale application.
Ce0.4Al0.1Zr0.5O1.95 was used as a support to prepare the Fe supported catalyst by complex copolymerization and liquid phase reduction methods, achieving uniform distribution of Fe atoms and increasing the highly active sites.
Under low temperature and low pressure conditions, the catalyst exhibits high ammonia synthesis activity, which reduces the pressure and temperature required for the reaction, reduces the production cost, and has long-term stability and suitable for industrial production.
Smart Images

Figure CN119753747A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ammonia synthesis, and in particular relates to a non-precious metal high electrical response ammonia synthesis catalyst and a method for synthesizing ammonia. Background Art
[0002] Synthetic ammonia is primarily produced via the Haber-Bosch process, which utilizes an iron-based catalyst to react N₂ and H₂ to produce ammonia under high temperature (400-600°C) and high pressure (15-30 MPa). Industrially, raw hydrogen is primarily obtained through high-pressure natural gas reforming. However, with increasing demands for greener and more sustainable production, future sources of hydrogen will gradually shift to renewable sources, such as those produced through water electrolysis or biomass. Due to the relatively low pressure of renewable hydrogen, developing high-performance catalysts at low temperatures and pressures to avoid the additional energy consumption associated with compressed gas has become crucial for achieving energy conservation, consumption reduction, and transformation and upgrading in the synthetic ammonia industry.
[0003] Although the Haber-Bosch process has been used industrially for over a century and has driven the development of the synthetic ammonia industry, it also has significant drawbacks. First, due to thermodynamic limitations, the conversion efficiency of nitrogen hydrogenation is low, typically between 10% and 15%. Even with process optimization, it can only reach around 30%. Second, the process is extremely energy-intensive, requiring high pressure (150-350 atm) and high temperature (350-550°C). The energy required for ammonia synthesis accounts for 1%-3% of the world's total energy consumption each year. Most importantly, the hydrogen required for ammonia synthesis is primarily derived from natural gas and steam cracking reforming, which not only consumes a large amount of natural gas resources but also results in significant CO2 emissions, severely impacting the environment.
[0004] To overcome the shortcomings of the Haber-Bosch process, scientists have proposed an electrocatalytic ammonia synthesis scheme. This scheme is based on the idea that ammonia synthesis can be achieved by providing suitable electron and proton sources. The reaction equation is: N2+6H + +6e→2NH3 However, existing electrocatalytic ammonia synthesis processes suffer from low Faradaic efficiencies, typically below 20%, resulting in low catalytic efficiency. Furthermore, while some precious metals (such as Ag, Au, and Ru) and their alloys are excellent catalysts, their high cost and limited availability preclude large-scale application. More importantly, most of these precious metal-based electrodes exhibit significant hydrogen evolution reaction performance, resulting in poor ammonia selectivity and low Faradaic efficiencies. Therefore, the development of highly active and stable non-precious metal catalysts has become a key research direction in the field of ammonia synthesis. Summary of the Invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a non-precious metal high electrical response ammonia synthesis catalyst and a method for synthesizing ammonia. Specifically, it provides an Fe-based catalyst with low price, abundant reserves and high physical and chemical stability, and Ce 0.4 Al 0.1 Zr 0.5 O 1.95 As a catalyst carrier, the catalyst of the present invention can be used to synthesize ammonia under low temperature and low pressure conditions in an external electric field enhanced thermal catalytic reaction, and has good application prospects.
[0006] To achieve the above object, the present invention provides the following technical solution: a non-noble metal high electrical response ammonia synthesis catalyst, comprising a carrier Ce 0.4 Al 0.1 Zr 0.5 O 1.95 and the active component Fe loaded on the carrier.
[0007] Furthermore, the content of Fe as an active component in the catalyst is 10 wt% to 30 wt%.
[0008] Furthermore, the content of Fe, an active component in the catalyst, is 12.5 wt%.
[0009] Furthermore, Ce was prepared by complex copolymerization. 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0010] Further, preparation of Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The specific steps of the carrier are: Ce(NO3)3·6H2O, ZrO(NO3)2·2H2O, and Al(NO3)3·9H2O in a stoichiometric ratio of 4:5:1 were added to the solvent to obtain a mixed solution 1; The product obtained by heating the mixed solution 1 to 320K~350K is dried and calcined to obtain Ce 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0011] Furthermore, the calcination temperature is 770 K~800 K.
[0012] Furthermore, Fe was loaded on Ce by liquid phase reduction method. 0.4 Al 0.1 Zr 0.5 O 1.95On the carrier.
[0013] Furthermore, Fe is loaded on Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The specific steps on the carrier are: preparing an aqueous solution of an Fe precursor; Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The carrier and the reducing agent are added to the aqueous solution of the Fe precursor, heated at 380K~420K and stirred to obtain a mixture; The mixture was filtered and dried to obtain Fe loaded on Ce. 0.4 Al 0.1 Zr 0.5 O 1.95 Catalyst on a support.
[0014] Furthermore, the reducing agent is a 10% N2H4 aqueous solution.
[0015] The present invention also provides a method for synthesizing ammonia, which is carried out using the above catalyst.
[0016] Furthermore, when the active component Fe content in the catalyst is 12.5 wt%, when the catalyst is used to synthesize ammonia, under the condition of applying an external electric field, at 0.9 MPa and 464 K, the ammonia synthesis rate is 2.3 mmol g −1 h −1 .
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides a non-precious metal high electrical response ammonia synthesis catalyst, using Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The support effectively inhibits the aggregation of Fe atoms, thereby increasing the number of active sites. Using non-precious metal Fe as the active component significantly reduces production costs. The catalyst of the present invention can be used in ammonia synthesis reactions, reducing the required pressure and temperature, making the reaction conditions milder and easier to implement, thus reducing the cost of industrialized ammonia production and making it suitable for widespread use. Furthermore, the catalyst of the present invention features a simple preparation method, mild conditions, highly controllable performance, excellent support stability, and low raw material costs, making it suitable for large-scale industrial production.
[0018] The synthetic ammonia catalyst of the present invention is prepared by a complex copolymerization method. 0.4 Al 0.1 Zr0.5 O 1.95 As a catalyst support, the obtained Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The carrier can effectively inhibit the agglomeration of Fe atoms, thereby increasing the number of active sites. Fe is then loaded onto Ce by liquid phase reduction. 0.4 Al 0.1 Zr 0.5 O 1.95 Compared with other loading methods, this method has good stability and large loading capacity, which can significantly improve the catalytic activity of the catalyst. When used at 0.9 MPa and 464K, the ammonia synthesis rate is 2.3 mmol g −1 h −1 Compared with other ammonia synthesis catalysts, the preparation method is simple and the preparation cycle is short. Compared with rare earth metal oxides, raw materials such as Ce(NO3)3·6H2O, ZrO(NO3)2·2H2O, Al(NO3)3·9H2O, and Fe(NO3)·9H2O are easily available and low-cost, making them more suitable for industrial applications. Furthermore, the catalyst provided by the present invention has long-term stability and can be reused multiple times. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the preparation process of the non-noble metal high electrical response ammonia synthesis catalyst of the present invention.
[0020] Figure 2 Figure 5 shows the ammonia activity and response voltage at different iron loading weights of the present invention (catalyst, 100 mg; reactant gas, N2:H2=1:3 (total flow rate, 240 SCCM); current: 6 mA; total pressure, 0.1 MPa; furnace temperature: 473 K).
[0021] Figure 3 The results of Fe / Ce with a loading of 12.5 wt% at different catalyst bed temperatures and total pressures with or without an electric field are shown in Figure 2. 0.4 Al 0.1 Zr 0.5 O 1.95 Ammonia synthesis rate of the catalyst (catalyst, 400 mg; reactant gas, N2 / H2 = 1:3; total flow rate, 960 sccm; current, 6 mA).
[0022] Figure 4 Fe / Ce obtained in Example 1 0.4 Al 0.1 Zr 0.5 O 1.95 Scanning electron microscopy (SEM) characterization of the catalyst. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0024] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0025] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0026] In the present invention, unless otherwise specified, percentages (%) or parts refer to percentages by weight or parts by weight relative to the composition.
[0027] In the present invention, unless otherwise specified, the components involved or their preferred components can be combined with each other to form a new technical solution.
[0028] In this disclosure, unless otherwise specified, the numerical range "a-b" is an abbreviation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "6-22" indicates that all real numbers between "6-22" are listed herein, and "6-22" is merely an abbreviation for these numerical combinations.
[0029] The "range" disclosed in the present invention is in the form of lower limit and upper limit, which can be one or more lower limits, and one or more upper limits respectively.
[0030] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0031] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the order. Preferably, the reaction method herein is carried out sequentially.
[0032] Unless otherwise indicated, the professional and scientific terms used herein are the same as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content can also be applied to the present invention.
[0033] The present invention provides a non-precious metal high electrical response ammonia synthesis catalyst with Ce 0.4 Al 0.1 Zr 0.5 O 1.95As a carrier, Fe serves as the active component and is loaded in the gaps between Ce, Zr and Al particles. By optimizing the preparation process, uniform distribution and minimal agglomeration of Fe particles are achieved, thereby improving the catalytic activity.
[0034] like Figure 1 As shown, the preparation method of the above-mentioned non-precious metal high electrical response ammonia synthesis catalyst comprises the following specific steps: S1 uses complex copolymerization to prepare Ce 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0035] First, dissolve ethylene glycol and citric acid monohydrate in distilled water and stir.
[0036] Then, Ce(NO3)3·6H2O, ZrO(NO3)2·2H2O, and Al(NO3)3·9H2O in a stoichiometric ratio of 4:5:1 were added to the solution and stirred. The solution was heated in a water bath at 320-350K, dried, and calcined at a temperature of 770K-800K to obtain Ce. 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0037] S2 uses liquid phase reduction method to load Fe on the prepared Ce 0.4 Al 0.1 Zr 0.5 O 1.95 On the carrier.
[0038] Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The carrier was dissolved in the aqueous solution of the Fe precursor and stirred for 1 h, then transferred to a heating platform and stirred for 2 h at a temperature of 380K~420K. During the stirring process, a 10% N2H4 aqueous solution was added as a reducing agent. The mixture was filtered and dried to obtain Fe / Ce 0.4 Al 0.1 Zr 0.5 O 1.95 catalyst.
[0039] When used in ammonia synthesis, the catalyst of the present invention maintains high ammonia synthesis activity in low-temperature, low-pressure environments under the application of an external electric field. This reduces the required pressure and temperature, making the reaction conditions milder and easier to implement, reducing the cost of industrialized ammonia production and making it suitable for widespread use. Furthermore, the catalyst of the present invention features a simple preparation method, mild conditions, highly controllable performance, excellent carrier stability, and low raw material costs, making it suitable for large-scale industrial production.
[0040] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] Example 1 The present invention provides a non-precious metal high electrical response ammonia synthesis catalyst, and the specific steps of the preparation method are as follows: S1 uses complex copolymerization to prepare Ce 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0042] First, ethylene glycol and citric acid monohydrate at a molar ratio of 2:1 were dissolved in distilled water and stirred to obtain a neutral solution.
[0043] Then, Ce(NO3)3·6H2O, ZrO(NO3)2·2H2O, and Al(NO3)3·9H2O in a stoichiometric ratio of 4:5:1 were added to the solution and stirred. The solution was heated in a water bath at 343K for 12h, dried, and calcined at 773K for 5h to obtain Ce. 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0044] S2 uses Fe(NO3)·9H2O as Fe precursor and adopts liquid phase reduction method to load Fe on the prepared Ce 0.4 Al 0.1 Zr 0.5 O 1.95 On the carrier.
[0045] First, 10.1 g of Fe(NO3)·9H2O was weighed to prepare an aqueous solution of Fe precursor, and 9.76 g of Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The carrier was dissolved in the aqueous solution of the Fe precursor and stirred for 1 h, then transferred to a heating platform and stirred for 2 h at 393 K. During the stirring process, a 10% N2H4 aqueous solution was added as a reducing agent. The mixture was filtered and dried to obtain Fe / Ce 0.4 Al 0.1 Zr 0.5 O 1.95 Catalyst, morphology such as Figure 4 As shown, the active component Fe content in the synthesized ammonia catalyst is 12.5 wt%, and the iron particle size is 24.8 nm; The present invention can accurately control the molecular weight distribution of the polymer through complex copolymerization; complex copolymerization can improve the efficiency and selectivity of the reaction, and by using specific catalysts or complexes, it can promote specific types of copolymerization reactions, thereby reducing the occurrence of side reactions and improving the yield and purity of the target polymer. The present invention adopts a liquid phase reduction method to assemble and control materials at the atomic and molecular levels, thereby better controlling the shape, particle size, particle size distribution and composition of nanoparticles; and the liquid phase reduction method has good versatility and can be used for the preparation of various metal nanoparticles. At the same time, the operation of this method is relatively simple and easy to implement in laboratories and industrial production. Adding a dispersant during the liquid phase reduction preparation stage can protect the powder from oxidation, control the powder particle size, and prevent the powder particles from agglomerating, thereby affecting the performance of the powder.
[0046] Example 2: The present invention provides a non-precious metal high electrical response ammonia synthesis catalyst, and the specific steps of the preparation method are as follows: S1 uses complex copolymerization to prepare Ce 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0047] First, ethylene glycol and citric acid monohydrate at a molar ratio of 2:1 were dissolved in distilled water and stirred to obtain a neutral solution.
[0048] Then, Ce(NO3)3·6H2O, ZrO(NO3)2·2H2O, and Al(NO3)3·9H2O in a stoichiometric ratio of 4:5:1 were added to the solution and stirred. The solution was heated in a water bath at 343K for 12h, dried, and calcined at 773K for 5h to obtain Ce. 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0049] S2 uses Fe(NO3)·9H2O as Fe precursor and adopts liquid phase reduction method to load Fe on the prepared Ce 0.4 Al 0.1 Zr 0.5 O 1.95 On the carrier.
[0050] First, 10.1 g of Fe(NO3)·9H2O was weighed to prepare an aqueous solution of Fe precursor, and 12.54 g of Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The carrier was dissolved in the aqueous solution of the Fe precursor and stirred for 1 h, then transferred to a heating platform and stirred for 2 h at 393 K. During the stirring process, a 10% N2H4 aqueous solution was added as a reducing agent. The mixture was filtered and dried to obtain Fe / Ce 0.4 Al 0.1 Zr 0.5 O 1.95 Catalyst, the active component Fe content in the synthesized ammonia catalyst is 10wt%.
[0051] Example 3: The present invention provides a non-precious metal high electrical response ammonia synthesis catalyst, and the specific steps of the preparation method are as follows: S1 uses complex copolymerization to prepare Ce 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0052] First, ethylene glycol and citric acid monohydrate at a molar ratio of 2:1 were dissolved in distilled water and stirred to obtain a neutral solution.
[0053] Then, Ce(NO3)3·6H2O, ZrO(NO3)2·2H2O, and Al(NO3)3·9H2O in a stoichiometric ratio of 4:5:1 were added to the solution and stirred. The solution was heated in a water bath at 343K for 12h, dried, and calcined at 773K for 5h to obtain Ce.0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
[0054] S2 uses Fe(NO3)·9H2O as Fe precursor and adopts liquid phase reduction method to load Fe on the prepared Ce 0.4 Al 0.1 Zr 0.5 O 1.95 On the carrier.
[0055] First, 10.1 g of Fe(NO3)·9H2O was weighed to prepare an aqueous solution of Fe precursor, and 3.25 g of Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The carrier was dissolved in the aqueous solution of the Fe precursor and stirred for 1 h, then transferred to a heating platform and stirred for 2 h at 393 K. During the stirring process, a 10% N2H4 aqueous solution was added as a reducing agent. The mixture was filtered and dried to obtain Fe / Ce 0.4 Al 0.1 Zr 0.5 O 1.95 Catalyst, the active component Fe content in the synthesized ammonia catalyst is 30wt%.
[0056] Figure 2 The activity and response voltage of the catalyst for ammonia synthesis at different Fe loading weights are shown. The amount of catalyst used in the test is 100 mg, the gas composition is N2:H2=1:3, and the flow rate is 240 Ncm 3 / min, current is 6mA, total pressure is 0.1MPa, furnace temperature is 473K. When the reaction conditions remain unchanged and only the Fe loading weight of the catalyst is changed, it can be seen that when the Fe loading is 12.5 wt%, the catalyst response voltage is the highest and the catalytic activity is also the highest.
[0057] Figure 3 Fe / Ce prepared in Example 1 0.4 Al 0.1 Zr 0.5 O 1.95 The performance of the catalyst was tested at different temperatures and total pressures (0.1, 0.5, and 0.9 MPa) with and without an electric field. A DC power supply of 6 mA was applied, and at 0.9 MPa and 464 K, the ammonia synthesis rate was 2.3 mmol g −1 h −1 The ammonia synthesis rate achieved is the highest ever achieved under such mild conditions. The results demonstrate that the optimized electric field Fe-based catalyst achieves a high ammonia synthesis rate under mild conditions, making it suitable for on-site, on-demand production.
[0058] In summary, the catalyst provided by the present invention uses the non-precious metal Fe as its active component, reducing production costs. Prepared through complex copolymerization and liquid-phase reduction, the catalyst features uniform Fe particle distribution, minimal agglomeration, and high catalytic activity. Even under the application of an external electric field, the catalyst maintains high ammonia synthesis activity at low temperature and low pressure, making it suitable for on-site, on-demand production.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A non-precious metal high electrical response ammonia synthesis catalyst, characterized in that: Including carrier Ce 0.4 Al 0.1 Zr 0.5 O 1.95 and the active component Fe loaded on the carrier.
2. The non-precious metal high electrical response ammonia synthesis catalyst according to claim 1, characterized in that: The content of Fe, an active component in the catalyst, is 10 wt% to 30 wt%.
3. The non-precious metal high electrical response ammonia synthesis catalyst according to claim 1, characterized in that: Preparation of Ce by complex copolymerization 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
4. The non-precious metal high electrical response ammonia synthesis catalyst according to claim 3, characterized in that: Preparation of Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The specific steps of the carrier are: Ce(NO3)3·6H2O, ZrO(NO3)2·2H2O, and Al(NO3)3·9H2O in a stoichiometric ratio of 4:5:1 were added to the solvent to obtain a mixed solution 1; The product obtained by heating the mixed solution 1 to 320K~350K is dried and calcined to obtain Ce 0.4 Al 0.1 Zr 0.5 O 1.95 carrier.
5. The non-precious metal high electrical response ammonia synthesis catalyst according to claim 4, characterized in that: The calcination temperature is 770 K~800 K.
6. A catalyst according to claim 1, characterized in that Fe was loaded on Ce by liquid phase reduction method. 0.4 Al 0.1 Zr 0.5 O 1.95 On the carrier.
7. The non-precious metal high electrical response ammonia synthesis catalyst according to claim 6, characterized in that: Fe is loaded on Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The specific steps on the carrier are: preparing an aqueous solution of a Fe precursor; Ce 0.4 Al 0.1 Zr 0.5 O 1.95 The carrier and the reducing agent are added to the aqueous solution of the Fe precursor, heated at 380K~420K and stirred to obtain a mixture; The mixture was filtered and dried to obtain Fe loaded on Ce. 0.4 Al 0.1 Zr 0.5 O 1.95 Catalyst on a support.
8. The non-precious metal high electrical response ammonia synthesis catalyst according to claim 7, characterized in that: The reducing agent is a 10% N2H4 aqueous solution.
9. A method for synthesizing ammonia, characterized in that: The method is carried out using the catalyst according to any one of claims 1 to 8.
10. A method for synthesizing ammonia according to claim 9, characterized in that: When the active component Fe content in the catalyst is 12.5 wt%, when the catalyst is used to synthesize ammonia, under the condition of applying 6 mA direct current, at 0.9 MPa and 464 K, the ammonia synthesis rate is 2.3 mmol g −1 h −1 .